Passive Control of Hydrodynamic Forces on a Circular Obstacle in a Transient Flow: FEM Computations - Ain, Qurrat Ul; Khan, Y.; Mahmood, Rashid; Alameer, A.; Majeed, Afraz Hussain; Faraz, N. (Frontiers in Physics, 2022)
Hydrodynamic forces are so crucial in engineering applications, various research initiatives have been carried out to limit them. A passive control technique to investigate the fluid forces acting on a circular cylinder in a laminar flow regime is studied in this paper. The reliability of the usage of splitter plate (passive control device) downstream the obstacle, in suppressing the fluid forces on a circular obstacle of diameter D=0.1m is presented. The first parameter of current study is the attachment of splitter plate of various length 〖(L〗_i) with the obstacle, whereas the gap separation 〖(G〗_i) between the splitter plate and the obstacle is used as a second parameter. The control element of first and second parameters are varied from 0.1 to 0.3. For the attached splitter plates of length 0.2 and 0.3, the oscillatory behavior of transient flow at Re=100 is successfully controlled. For the gap separation 0.1 and 0.2 similar results are obtained. However, it is observed that a splitter plate of too short length and a plate located at inappropriate gap from obstacle, are worthless. Moreover, the present study is extended for Power law fluid and maximum drag reduction is achieved by using the same strategy as mentioned above. A computational strategy based on the finite element method is utilised due to the complicated representative equations. For a clear physical depiction of the problem, velocity and pressure plots have been provided. Drag and lift coefficients the hydrodynamic benchmark values, are also evaluated in a graphical representation surrounding the obstacle’s peripheral surface as well as the splitter plate. As a conclusion, splitter plate can function to control fluid forces either it is attached or detached, based on plate length and gap separation between obstacle and plate, respectively.